CONVENTIONAL AND MOLECULAR STUDY OF Entamoeba spp. IN DOMESTIC DOG’S FECAL AT BAGHDAD CITY, IRAQ. - Fadhil, A. I.; Fadel, S. R.; Faraj, A. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to detect  Entamoeba spp. in domestic dogs by using the microscopic method and PCR. The study includes collection of 100 fecal samples by visiting a small animal private clinics in Baghdad, at the period from January 2019 to February 2020.  The microscopical results showed the rate of infection at Entamoeba spp. was (15%).  Show a higher infection rate in females (15.55%)) than in males (14.54%)without significant difference (P.0>0.05). The Prevalence of Entamoeba related to age was (22%), (6%) in young and adult age respectively. Molecular examination results, the total infection rate of  Entamoeba  in dogs fecal showed 15% . Ten positive PCR products were sequenced and deposited in the Genebank database, the first time in Iraq, the phylogenic analysis demonstrated that 10sequences belong to  Entamoeba histolytica (MT296770, MT296771, MT296772, MT296773, MT296774, MT296775, MT296776, MT296777, MT296778, and MT296779).